QUANTITATIVE EVALUATION OF INTERACTIONS OF TRANSCRIPTION FACTOR KAP1 AND HETEROCHROMATIN PROTEIN HP1 IN VIVO - Kulyyassov, A.T.; Zhubanova, G.S.; Ramanculov, E.M.; Ogryzko, V.V. (Eurasian Journal of Applied Biotechnology, 2014)
Protein-protein interactions (PPI) play a key role in many processes within the cell, and their affinity and specificity are fine-tuned with respect to the functions they perform. Disturbances in the signal transduction pathways associated with PPI lead to the development and progression of cancer. Study of protein-protein interactions not only improve our understanding the mechanism of the processes inside the cell, but also help in the search of small molecule modulators of PPI for the treatment of various types of tumors. We have used method, called the Proximity Utilizing Biotinylation (PUB), based on co-expression within a single cell of the recombinant proteins - the protein of interest fused with biotin ligase BirA and its partner with the biotin acceptor peptide BAP, which allows an accurate quantitative assessment of the extent of their interaction in vivo. The aim of this work is to develop a method for quantifying interactions in vivo of oncomarker proteins HP1a and transcription factor KAP1. In experiments on protein expression of BAP and BirA fusions of HP1a and KAP1 in HEK293T cells we found elevated levels of biotinylation due to in vivo interaction of proteins BAP-HP1a and BirA-wtKAP1. The ratio of biotinylation between BAP-HP1a in samples with BirA-mutKap1 and BirA-wtKap1 was 0,43±0,086. In reciprocal experiments, the level of biotinylation was higher in case of interaction between proteins BAP-wtKap1 and BirA-HP1a. The ratio of biotinylation of BAP-mutKap1 and BAP-wtKap1 in the presence of BirA-HP1 was 0,2±0,04.